Sexual identity fluidity, identity management stress, and depression among sexual minority adolescents - Srivastava, Ankur; Hall, William J.; Krueger, Evan A.; Goldbach, Jeremy T. (Frontiers in Psychology, 2023)
Introduction Sexual identity is mutable and evolving, particularly during adolescence. Sexual identity fluidity could be stressful for some adolescents and may differ by birth-sex. Evidence suggests chronic stress can lead to negative mental health outcomes. However, it is unknown if these two processes (stress and depression) differ by sexual identity fluidity. Methods This paper studied time-sequential associations between identity management stress and depression over time by sexual identity fluidity, in a national longitudinal data from sexual minority adolescents (SMA) aged 14–17 years using a multigroup autoregressive cross-lagged model (n = 1077). Results In the sample, 40% of SMA reported at least one change in sexual identity over 18-month period. Greater number of cisgender females reported sexual identity fluidity compared to their male counterparts (46.9% vs. 26.6%). A temporal cross-lagged effect was reported between depression and identity management stress among cisgender females who reported fluidity in sexual identity; and no cross-lagged effect was reported among those females who did not report fluidity. However, among cisgender male sample depression predicted subsequent identity management stress, irrespective of their change sexual identity fluidity status. Conclusion Public health programs and practice must be responsive to the sexual identity fluidity processes among adolescents, with particular attention to minority stress and depression. In addition, our results indicate that sexual identity development and fluidity processes differ between cisgender females and males; and the nuances associated with these processes of change need further investigation.